STRATEGI CLEAN CLOTHES CAMPAIGN DALAM MENGADVOKASI HAK BURUH PEREMPUAN DI INDUSTRI FAST FASHION: STUDI KASUS JABA GARMINDO DI INDONESIA - Salsabilla, Dhiyya; Iskandar, Irwan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2026)
This research analyzes Clean Clothes Campaign's (CCC) transnational advocacy for women workers' severance rights at PT Jaba Garmindo. Utilizing a qualitative case study and the Transnational Advocacy Network (TAN) framework, it examines the use of information, symbolic, leverage, and accountability politics via a boomerang pattern against Uniqlo and s.Oliver. Findings reveal that these strategies secured partial financial relief from s.Oliver but faced resistance from Uniqlo. The study concludes that non-state actors' effectiveness in global governance is constrained by voluntary compliance and power asymmetries within buyer-driven supply chains. Keywords: Clean Clothes Campaign, Women Workers, Fast Fashion, Transnational Advocacy Network, Jaba Garmindo.